The martial arts - Terry, C. M. (Physical Medicine & Rehabilitation Clinics of North America, 2006)
Content of the article: Background History Styles Participant profile Training methods Individual or noncontact group practice Warm-up Basics Falls Rolls Kata Equipment Sparring gear Floor mats Heavy bags Targets Breaking Miscellaneous equipment Weapons Partner work Injuries Epidemiology of injuries Types of injuries, prevention, and return to martial arts training after an injury Skin or soft tissue injuries Head and neck Trunk Upper extremities Lower extremities Benefits of training in the martial arts Disabled martial artists Summary Acknowledgements References